Traffic Performance Analysis of u-turn and Fly Over u-turn Scenario; A Case Study at Soekarno Hatta Road, Palembang, Indonesia. (2015) - Della, Rhaptyalyani H.; Hanafiah,; Arliansyah, Joni; Artiansyah, Riga
Abstract: On section of road often more than one U-turn median opening that operates, but sometimes this make long queue in some periods time. It's causing many factors like on- coming speed and maneuver that make waiting time. Basically, no procedure or guideline for U-turn sections design. The attempted to find the optimal approach regarding acceptances gap that occurs at U-turn median opening and the appropriate application criteria for the road that use U-turn median opening based on the capacity and traffic demand existing in the U-turn median opening. Gap acceptances influential for operational of U-turn, where the vehicle while performing maneuvers will decrease the speed of vehicles. The evaluation of the delay and travel time will provide to know the performance of the U-turn median opening. The purpose of this study is to evaluation the performance of U-turn median opening with study case at Soekarno Hatta Road, Palembang, Indonesia. The specific objectives in this study are to find the operational performance of U-turn movement by delay and travel time analysis by HCM 2000 and to evaluate the performance of U-turn using Vissim Simulation program. Vissim Simulation used for simulated 2 difference of width median opening and U-turn fly over. Simulated case study using Vissim simulation with different of width median opening showed in narrow width median opening will make major delay and the high of travel time. Based on the comparison of four scenarios of U-turn models and existing model. The best performance of U-turn facilities showed on 4th model. The 4th model is U-turn with fly over design, showed the performance are saturation degree 0.7333, delay study 3, 43905, delay vissim 3, 133479, and the travel time is 526, 20. The travel time would lower with an increasingly the width of median opening. Simulation showed that travel time and delay slight differences when the width of median opening large than existing U-turn. Then comparison from U-turn with road median opening design and fly over U-turn design showed the last design give the best in traffic performance.